An Elliptic Curve Signcryption Scheme and Its Application. (6th May 2022) - Zhang, Ping; Li, Yamin; Chi, Huanhuan
Abstract : Two basic security requirements in communication are confidentiality and authentication. Signcryption is an ideal technique to transmit encrypted and authenticated data. In view of the shortcomings of existing signcryption schemes and the high security of elliptic curve cryptography (ECC), we design a ECC-based signcryption scheme and evaluate it in terms of security, computational overhead, and communication overhead. Finally, we consider the application of our secure and efficient signcryption scheme in the smart lock key management system and analyze the bit-oriented performance of the designed key management scheme.